Association between Circulating Fibroblast Growth Factor 23, α-Klotho, and the Left Ventricular Ejection Fraction and Left Ventricular Mass in Cardiology Inpatients - Shibata, Kensaku (Public Library of Science, 2013)
BACKGROUND: Fibroblast growth factor 23 (FGF23), with its co-receptor Klotho, plays a crucial role in phosphate metabolism. Several recent studies suggested that circulating FGF23 and α-Klotho concentrations might be related to cardiovascular abnormalities in patients with advanced renal failure. PURPOSE: Using data from 100 cardiology inpatients who were not undergoing chronic hemodialysis, the association of circulating levels of FGF23, α-Klotho, and other calcium-phosphate metabolism-related parameters with the left ventricular ejection fraction (LVEF) and left ventricular mass (LVM) was analyzed. METHODS AND RESULTS: LVEF was measured using the modified Simpson method for apical 4-chamber LV images and the LVM index (LVMI) was calculated by dividing the LVM by body surface area. Univariate analysis showed that log transformed FGF23, but not that of α-Klotho, was significantly associated with LVEF and LVMI with a standardized beta of −0.35 (P<0.001) and 0.26 (P<0.05), respectively. After adjusting for age, sex, estimated glomerular filtration rate, and serum concentrations of intact parathyroid hormone, and 25-hydroxyvitamin D as covariates into the statistical model, log-transformed FGF23 was found to be a statistically positive predictor for decreased left ventricular function and left ventricular hypertrophy. CONCLUSIONS: In cardiology department inpatients, circulating FGF23 concentrations were found to be associated with the left ventricular mass and LVEF independent of renal function and other calcium-phosphate metabolism-related parameters. Whether modulation of circulating FGF23 levels would improve cardiac outcome in such a high risk population awaits further investigation.